Stretchable, self‐healable, and breathable biomimetic iontronics with superior humidity‐sensing performance for wireless respiration monitoring. Issue 2 (26th August 2022) - Ding, Qiongling; Wang, Hao; Zhou, Zijing; Wu, Zixuan; Tao, Kai; Gui, Xuchun; Liu, Chuan; Shi, Wenxiong; Wu, Jin
Abstract: Stretchable, self‐healing, and breathable skin‐biomimetic‐sensing iontronics play an important role in human physiological signal monitoring and human–computer interaction. However, previous studies have focused on the mimicking of skin tactile sensing (pressure, strain, and temperature), and the development of more functionalities is necessary. To this end, a superior humidity‐sensitive ionic skin is developed based on a self‐healing, stretchable, breathable, and biocompatible polyvinyl alcohol–cellulose nanofibers organohydrogel film, showing a pronounced thickness‐dependent humidity‐sensing performance. The as‐prepared 62.47‐μm‐thick organohydrogel film exhibits a high response (25, 000%) to 98% RH, excellent repeatability, and long‐term stability (120 days). Moreover, this ionic skin has excellent resistance to large mechanical deformation and damage, and the worn‐out material can still retain its humidity‐sensing capabilities after self‐repair. Humidity‐sensing mechanism studies show that the induced response is mainly related to the increase of proton mobility and interfacial charge transport efficiency after water adsorption. The superior humidity responsiveness is attributed to the reduced thickness and the increased specific surface area of the organohydrogel film, allowing real‐time recording of physiological signals. Notably, by combining with a self‐designed printed circuit board, a continuous and wireless respiration monitoring system is developed, presenting its great potential in wearable and biomedical electronics. Abstract : Stretchable, self‐healable, and breathable biomimetic ionic skin with superior humidity‐sensing performance is developed based on fully physical cross‐linked organohydrogel film, which features a superior responsiveness, excellent repeatability, and long‐term stability. Particularly, it can be used for real‐time and remote respiration monitoring and to implement a breathing interruption alarm system for sleep apnea syndrome patients after combining with a specially designed circuit and mask, showing its great potential in wearable and biomedical electronics.